Cadmium nitrate and DNA methylation in gastropods: comparison between ovotestis and hepatopancreas - George A. Draghici; Cristina A. Dehelean; Alina E. Moaca; Marius L. Moise; Iulia Pinzaru; Valentin N. Vladut; Ioan Banatean-Dunea; Dragos Nica (PeerJ, 2023)
Dietary ingestion is the main route of exposure to hazardous contaminants in land animals. Cadmium, a high-profile toxic metal, affects living systems at different organismal levels, including major storage organs (liver, kidneys), key organs for species survival (gonads), and epigenetic networks regulating gene expression. 5-methylcytosine (5mC) is the most common and best-characterized epigenetic mark among different modified nucleosides in DNA. This important player in methylation-driven gene expression is impacted by cadmium in sentinel terrestrial vertebrates. However, limited information exists regarding its impact on macroinvertebrates, especially land snails commonly used as (eco)toxicological models. We first investigate the methylomic effects of dietary cadmium given as cadmium nitrate on terrestrial mollusks. Mature specimens of the common brown garden snail, Cornu aspersum, were continuously exposed for four weeks to environmentally-relevant cadmium levels. We determined global genomic DNA methylation in hepatopancreas and ovotestis, as well as changes in the methylation status of CG pairs at the 5′ region close to the transcription site of gene encoding the Cd-selective metallothionein (Cd-MT). Weight gain/loss, hypometabolism tendency, and survival rates were also assessed. Although this exposure event did not adversely affect survival, gastropods exposed to the highest Cd dose revealed a significant reduction in body weight and a significant increase in hypometabolic behavior. The hepatopancreas, but not the ovotestis, displayed significant hypermethylation, but only for the aforementioned specimens. We also found that the 5′ end of the Cd-MT gene was unmethylated in both organs and its methylation status was insensitive to cadmium exposure. Our results are important since they provide scientists, for the first time, with quantitative data on DNA methylation in gastropod ovotestis and refine our understanding of Cd epigenetic effects on terrestrial mollusks.